Time and Dose Dependent Augmentation of Inhibitory Effects of Abciximab by Aspirin - Schneider, David J.; Baumann, Patricia Q.; Holmes, Michael B.; Taatjes, Douglas; Sobel, Burton E. (Thrombosis and Haemostasis, 2001)
Aspirin and abciximab independently decrease the incidence of cardiac events. To identify potential interactions, antiplatelet effects of abciximab were characterized in blood from healthy subjects given aspirin. Platelet activation was determined in whole blood with and without abciximab (2 μg/ml) added in vitro. Flow cytometry was used to quantify fibrinogen binding (glycoprotein IIb-IIIa activation). Binding of fluorochrome-labeled and 125I-labeled abciximab was determined before and after exposure to aspirin. In blood from subjects given aspirin for 5 days, abciximab-induced inhibition of the capacity to bind fibrinogen in response to 1 μM ADP was greater when the daily dose had been 325 mg compared with 81 mg (% inhibition: no aspirin 53 ± 6; 81 mg daily 62 ± 5; 325 mg daily 69 ± 6). The effect of 5 daily doses of aspirin was greater than that of one. Larger single doses elicited larger effects (% inhibition 2 h after 325 mg 59 ± 6; 2 h after 650 mg 78 ± 5). Neither salicylsalicylic acid nor naproxen sodium potentiated the effect of abciximab. Exposure of platelets to 14Cacetylsalicylic acid led to acetylation of glycoprotein IIb and IIIa. Binding of 125I-abciximab to platelets was increased after 30 and 60 min. Acetylation of glycoprotein IIb-IIIa by aspirin augments inhibitory effects of abciximab in a dose- and time-dependent manner by increasing binding of abciximab to platelets.
Keywords: Platelets; glycoproteins; aspirin; platelet aggregation inhibitors